Pengaruh Celebrity Endorser Jerome Polin Terhadap Keputusan Pembelian Mie Sedap Tasty Beef Yakiniku: (Survei Pada Followers Instagram @miesedaaptasty) - Purnamasari, Oktaviana; Solicha, Siti Robiatus (Jurnal Netnografi Komunikasi, 2023)
Advertising is a tool used as a communication process to convey information to audiences that can generate attention, interest and decisions on actions to buy the products offered. The use of celebrity endorsers in advertisements is the main attraction of a brand to the intended target market, as well as building a strong emotional relationship with consumers. The purpose of this study was to determine 1) Jerome Polin as a celebrity endorser for Sedaap Tasty Beef Yakiniku noodle products, 2) Purchase decisions and 3) The influence of celebrity endorser Jerome Polin on purchasing decisions for Sedaap Tasty Beef Yakiniku Noodles. This study uses a quantitative approach with a survey method with a questionnaire as the data collection instrument. The population in this study were followers of the Instagram account @miesedaaptasty with a population of 120 and a sample of 55 people. The sampling technique used simple random sampling technique. The results showed that celebrity endorser Jerome Polin had t-count (10.796) > t-table (2.398), it was stated that there was an influence between Celebrity Endorser Jerome Polin on the Purchase Decision of Sedaap Tasty Beef Yakiniku Noodles. Meanwhile, the R square result is 0.687, which means that Celebrity Endorser Jerome Polin influences the Purchase Decision of Mie Sedaap Tasty Beef Yakiniku by 68.7%, and the remaining 31.3% is influenced by other factors outside of this study.